PEMANFAATAN HALAMAN SEKOLAH SEBAGAI TAMAN EDUKASI PADA PUSAT KEGIATAN PAUD UMANAA KELURAHAN ANTANG KECAMATAN MANGGALA KOTA MAKASSAR - Nashrah Arsyad; Juhana Said (Universitas Trisakti, 2021)
The utilization of the schoolyard in the learning process involves the creation of the teacher in utilizing and practicing it as a learning medium. This, coupled with the support of the student's guardians, will complement the achievement of educational goals in early childhood. This activity aims to provide education in the form of counseling and training on the use of schoolyards as educational media so that managers, teachers, and parents of students can understand the importance of the existence of a schoolyard, and besides, that they can also understand how to use the schoolyard as an educational medium for children, students, increase the desire and cooperation of managers, teachers, and parents of students to create a comfortable environment by utilizing and arranging a beautiful and educational schoolyard. To achieve the goals and objectives, this activity is carried out using providing education in the form of counseling and training. The results of the implementation of this activity help increase the knowledge, insight, skills, and creativity of teachers, students, and guardians of students in the use and arrangement of the schoolyard as an educational park which also supports the creation of a beautiful yard environment.